Identificação e avaliação de vazios urbanos na área continental do município de São Vicente (SP): potencialidades e possibilidades de uso - Carol, Francisco José (2005)
This paper promotes an investigation into the Peripheral Urban Emptiness through identification and analysis of the existing cases in São Vicente s Municipality Continental Area, spatial field of study. Its main objective is the establishment of specific guidelines for these urban emptiness, this way contributing to the municipality s urban environmental planning. To this end it was carried out documental research and in loco collection of data which allowed the physical characterization of the spaces studied. This first stage of investigation was complemented and related to the study of the laws incidental to São Vicente s Continental Area, presenting as its first result considerations over the possibilities of use and occupancy for each one of the eleven empty spaces found. The research s final product is composed of suggestions for altering the zoning of use and occupancy of the soil concerned with the area of study specified, with the creation of new zones of use and new proposals for those areas identified as urban emptiness.